1905 Ga. Laws 86 - (:unkn) unknown (My University, 1905)
Rocking or Shooting at or in Cars, § 1: Prohibited throwing rocks or other missiles at, towards, or into any passenger train on a railroad. Also Prohibited shooting any gun, pistol, or firearms of any kind towards or into any such car or while in any such car/ Violators imprisoned one to five years
Keywords: DISCHARGE